Original models for the prediction of angular error in wire-EDM taper-cutting - Plaza, S.; Ortega, N.; Sanchez, J. A.; Pombo, I.; Mendikute, A. (International journal of advanced manufacturing technology, 2009)
Taper-cutting is a common application of the wire electrical discharge machining (WEDM) process used for the production of parts with complex geometry such as extrusion dies in wear-resistant materials, cutting dies, etc. During cutting, the wire is subject to deformation, resulting in deviations in the inclination angle of machined parts. This fact causes dimensional errors and loss of tolerances that can lead to the rejection of high added-value tooling. Currently, WEDM machine manufacturers propose time-consuming experimental trial-and-error methodologies for the correction of the errors. To reduce the experimental load and to contribute a more general approach to the problem, two original models for the prediction of angular error in WEDM taper-cutting are presented here. Results show that part thickness and taper angle are the most influencing variables in the problem. Experimental validation of the proposed models shows that angular error can be reduced below 3′45′′ in 75% of cases.